Bug stew! - Jordan, Apple; Cuddy, Robbin; Walt Disney Company (New York : Random House, 2003)
An easy-to-read, rhyming tale of Timon, Pumbaa, and Simba, who spend a day searching for and eating all sorts of tasty bugs.
At head of title: Disney's the Lion King.
Preschool-Kindergarten.
Keywords: Simba (Fictitious character : Disney) -- Juvenile fiction; Insects -- Juvenile fiction; Lions -- Juvenile fiction; Warthog -- Juvenile fiction; Meerkat -- Juvenile fiction; Simba (Fictitious character : Disney) -- Fiction; Insects -- Fiction; Lions -- Fiction; Warthog -- Fiction; Meerkat -- Fiction; Stories in rhyme; Africa -- Juvenile fiction; Africa -- Fiction; Stories in rhyme